Recent advances in the use of high flow nasal oxygen therapies - Wyatt, Kara D.; Goel, Neha N.; Whittle, Jessica S. (Frontiers in Medicine, 2022)
High flow nasal oxygen is a relatively new option for treating patients with respiratory failure, which decreases work of breathing, improves tidal volume, and modestly increases positive end expiratory pressure. Despite well-described physiologic benefits, the clinical impact of high flow nasal oxygen is still under investigation. In this article, we review the most recent findings on the clinical efficacy of high flow nasal oxygen in Type I, II, III, and IV respiratory failure within adult and pediatric patients. Additionally, we discuss studies across clinical settings, including emergency departments, intensive care units, outpatient, and procedural settings.